The Role of a Notary for Construction Service Providers on Failed to Build Disputes - Sanny, Dewa Afrizal (Jurnal Konstatering, 2023)
The 1999 Construction Services Law and the 2017 Construction Services Law realize that the implementation of construction services is a complex matter and involves many interests, so in the event of a building failure a party is needed who is able to provide an objective and professional view regarding responsibility for the failure. This thesis research was carried out using sociological juridical because it was carried out by collecting various data. The efforts to resolve the construction failure dispute in Madiun City have not been carried out based on the rules Act No. 2 of 2017 related to Construction Services, Legal protection for construction service providers in construction failure disputes caused by third parties in Madiun City still has weaknesses, namely the limited protection of the position of construction service providers from criminal threats due to the absence of criminal sanctions, as well as weaknesses in the form of most of the agreements for the use of building construction services that were made were not agreements made by deed before a notary. Keywords: Dispute; Legal; Protection.